Laparoscopic treatment for adult inguinal hernia with cryptorchidism: A case report. (2020) - Wakabayashi, Masakazu; Aoki, Kana; Yoshida, Hayato; Kimura, Tomohiro; Domoto, Yoshinori; Hosaka, Miki; Funatsu, Kentarou; Aisaki, Kazuo; Hokari, Takeo
Highlights: Cryptorchidism is the most common disorder of male children, which is often diagnosed and treated during childhood. A case of adult inguinal hernia with cryptorchidism is rare condition. TAPP and simultaneous laparoscopic orchiectomy for inguinal hernia with cryptorchidism were safe and feasible. Abstract: Introduction: Cryptorchidism or undescended testis is the most common disorder of male children, which is often diagnosed and treated during childhood. Adult patients with cryptorchidism are uncommon. Herein we report the case of adult inguinal hernia with cryptorchidism successfully treated by laparoscopic surgery simultaneously. Presentation of case: We report a case of 68 year-old-man who was admitted to our hospital with a complaint of bulge and pain in the right groin area from 2 weeks before. CT or MRI revealed a right inguinal hernia and an undescended testis in the right inguinal canal. He was diagnosed with right inguinal hernia accompanied by cryptorchidism. Laparoscopic transabdominal preperitoneal repair (TAPP) and orchiectomy were performed simultaneously. Postoperative period was uneventful and he was discharged home on the 1st postoperative day. Pathological examination of the specimen was reported as atrophic testis with no malignancy. There has been no recurrence during a follow-up. Discussion: To our Knowledge, the case report of adult inguinal hernia with cryptorchidism treated by laparoscopic surgery is rare. All cases recommended the feasibility of laparoscopic surgery. Conclusion: Adult inguinal hernia with cryptorchidism is a rare condition. TAPP and simultaneous laparoscopic orchiectomy for inguinal hernia with cryptorchidism were safe and feasible. It could be the first surgical option for the treatment of such adult patients.